Micro, Small and Medium Enterprises Financing in Islamic Rural Banks in Indonesia - Alvira Aina A'yun (Institut Agama Islam Negeri (IAIN) Curup, 2020)
Purpose: Purpose of this paper to analyze relation between internal factorsconsist of CAR, ROA, ROE, NPF, BOPO and external factors consist of Inflation, Interest rate, exchange rate that influence Islamic Rural Bank financing to Small Medium Enterprises.Design/Method/Approach: This paper use financing SME data from Islamic Rural Bank, internal and external factor from Islamic Rural Bank in 2010-2018. The paper use vector autoregression if stasioner in level an use vector error correction model of stasioner and cointegration in first difference. Use IRF and VD analysis to predict in the future.Findings: Results indicate that inflation, interest rate, NPF and BOPO have long term effect in SME financing an in short term only NPF influencing in SME financing.Originality/Values: Islamic finance industry one of industry that very important, this paper adds to understand Islamic finance industry which has received limited attention. Novelty in this paper use SME financing in Islamic rural bank, inflation, exchange rate, interest rate.